CD4-1 and CD4-2 single positive are two major CD4 lymphocyte subpopulations in ginbuna crucian carp Carassius auratus langsdorfii - Lau, Lik Ming; Misato, Kuga; Motohiko, Sano; Goshi, Kato (Elsevier B.V., 2023)
In this study, we established a murine cell line that expresses ginbuna crucian carp (ginbuna) CD4-2 and used it to develop an anti-CD4-2 monoclonal antibody (mAb). An established mAb, named D5, showed good reactivities to BALB/c 3T3 cells expressing CD4-2 and a lymphocyte population in the ginbuna leukocytes. Gene expression analysis showed that D5+ cells express CD4-2 and TCRβ genes but not CD4-1 and IgM genes, meanwhile May Grunwald-Giemsa staining of sorted D5+ cells had the typical morphology of lymphocytes. Two-color immunofluorescence analysis with anti-CD4-1 mAb (6D1) and anti-CD4-2 mAb (D5) by flow cytometry revealed that the percentages of CD4-1 single positive (SP) and CD4-2 SP lymphocytes were comparatively higher than CD4-1/CD4-2 double positive (CD4 DP) lymphocytes in all tissues examined in ginbuna. The highest percentage of CD4-2 SP cells (~40%) was found in the thymus, while the head-kidney exhibited the highest percentages of CD4-1 SP (~30%) and CD4 DP (~5%) cells. These findings indicated that ginbuna CD4+ lymphocyte population consists of two major subpopulations (CD4-1 SP and CD4-2 SP) and a minor subset (CD4 DP).